Вы находитесь на странице: 1из 5

# 6.

## (1) A = TDT-1 = TT-1

where 1,…,m are the eigenvalues of A and v1,…vm are the corresponding eigenvectors
and
T = matrix whose columns are v1,…vm

## We also saw how this led to a corresponding formula An, i.e.

(2) An = TDnT -1 = TT -1

These formulas are still valid if A has complex eigenvalues. However, if the entries of A
are real and A has complex eigenvalues, then it expresses An in terms of complex
numbers and some of the qualitative properties of An are not obvious. There is a variation
of (1) and (2) for real matrices with complex eigenvalues which express A and An in
terms of real numbers and certain properties of A and An are more obvious. For
simplicity we restrict our attention to 22 matrices.

## Theorem 1. Suppose A is a 22 matrix with eigenvalues 1 =  + i and 2 =  - i

where  and  are real. Let the corresponding eigenvectors be v1 = p + iq and v2 = p – iq
where p = and q = are vectors with real entries. Then

(3) A = TRT-1 = -1

-1
(4) A =

where r and  are the polar coordinates of the point in the plane whose Cartesian
coordinates are , i.e. r = and  = angle makes with the positive x axis.

Remarks. T is the matrix whose columns are the real and imaginary parts of v2 = p – iq
the eigenvector corresponding to 2 =  - i. R is the matrix for a rotation by an angle 
followed by a stretching or compression by a factor of r. So A acts like an "oblique"
rotation by an angle  followed by a stretching or compression by a factor of r.

Proof. Since Av1 = 1v1 one has A(p + iq) = ( - i)(p + iq). Expanding out one has
Ap + iAq = (p - q) + (q + p)i. Identifying real and imaginary parts one has
Ap = p - q and Aq = p + q. These two formulas can be written as Ap = p + (- q)
and A(- q) = (- )p + (- q).

6.5 - 1
The columns of AT are A times columns of T, i.e. Ap = p + (- q) and
A(- q) = (- )p + (- q). The columns of TR are linear combinations of the columns of T
using the entries of the columns of R as the coefficients. These work out to be p + (-
q) and - )p + (- q). Thus AT = TR. Multiplying both sides by T-1 gives (1).

The formula (4) follows from (3) and the relation between the polar and Cartesian
coordinate of a point, i.e.  = r cos  and  = r sin . //

## Example 1. Let A = . In Example 1 of section 6.3 we saw that A has eigenvalues 1 = -

2 + 5i and 2 = - 2 - 5i and eigenvectors v1 = and v2 = . So  = -2,  = 5, p = and q = .
Thus T = and R = = where  =  - tan-1  1.95  111.8. So
-1 -1
A = =

## Let's check (3). One has

TRT-1 = -1
=

= =

= = = A

Now let's see how the formula (4) leads to a corresponding formula for An.

## Theorem 2. Suppose A is a 22 matrix with eigenvalues 1 =  + i and 2 =  - i

where  and  are real. Let the corresponding eigenvectors be v1 = p + iq and v2 = p – iq
where p = and q = are vectors with real entries. Then

(5) An = TRnT-1 = -1

where r and  are the polar coordinates of the point in the plane whose Cartesian
coordinates are .

Proof. The formula (3) implies An = TRnT-1 using the same argument as in section 6.3.
One has Rn = (rR)n = rn(R)n, where R = is the matrix for a rotation by an angle .
Using the addition formulas for sine and cosine it is not hard to show that RR = R+ and
hence (R)n = Rn = . Thus Rn = rn = . Combined with An = TRnT-1 this proves (5). //

There is an alternate proof of Theorem 2 that is based on the following proposition and
properties of the polar form of complex numbers.

6.5 - 2
Proposition 3. If  is an eigenvalue of A with eigenvector v, then n is a eigenvalue of
An also with eigenvector v.

## Proof. This is proved by induction on n. By hypothesis it is true for n = 1. Suppose it is

true for n. Then An+1v = AnAv = Anv = Anv = (nv) = n+1v, so the result is true for
n + 1. By induction it is true for all positive n. //

Alternative proof of Proposition 2. By Proposition 3 one has (1)n and (1)n are
eigenvalues of An with eigenvectors v1 = p + iq and v2 = p – iq. By Proposition 4 below rn
and n are the polar coordinates of (1)n. So Theorem 2 follows from Proposition 1
applied to An. //

Example 2. Find An if A = .

-1
A =

## where c = cos , s = sin  and  =  - tan-1. So

An = 29n/2-1 =
= =
where cn = cos (n) and sn = sin(n).

Problem 1. The eigenvalues of A = are 1 = 1 + i and 2 = 1 - i and the corresponding eigenvectors are v1
= and v2 = . Find a formula for An that displays the entries as sums of multiples of things of the form rn
cos(n) or rn sin(n).

## Example 3. Solve the difference equations

xn+1 = - xn - 26yn
yn+1 = xn - 3yn
along with the initial conditions x0 = 2 and y0 = 1.

One has

= = = A

## where A is as in example 2. The solution is

n n
= = =
= =

6.5 - 3
where c = cos , s = sin  and  =  - tan-1. So

## xn = (10 cos  - 24 sin )

yn = (5 cos  + sin )

Problem 2. The eigenvalues of A = are 1 = 1 + i and 2 = 1 - i and the corresponding eigenvectors are v1
= and v2 = . Find formulas for the solution of the difference equations
xn+1 = - 2yn
yn+1 = xn + 2yn
along with the initial conditions x0 = 1 and y0 = 3. Your formulas for xn and yn should be sums of multiples
of things of the form rn cos(n) or rn sin(n). (This is a continuation of Problem 1 above.)

## Polar Representation of Complex Numbers. The complex number z = x + yi can be

associated with the point u = in the plane. The polar coordinates of u are used to define
the absolute value and argument of z.

|z| =
= absolute value of z
= polar coordinate r of u =
= distance of u from the origin

arg(z) = argument of z
= polar coordinate  of u =
= angle u makes with the positive x axis
=

Then

## z = x + yi = r cos  + r (sin ) i = r (cos  + i sin ) = rei

where
ei = cos  + i sin 

## Example 4. If z = 2 + 3i then | z | = and arg(z) = tan-1(1.5)  0.993 so the polar

representation of 2 + 3i is

## 2 + 3i = (cos(tan-1(1.5) + (sin(tan-1(1.5)) i) = etan-1(1.5)i

When one multiplies complex numbers the absolute values multiply and the arguments

6.5 - 4
Propostion 4. If z = r (cos  + i sin ) and w = s (cos  + i sin ) then

## Multiplying out the left side one has

(cos + i sin)(cos + i sin) = (cos cos - sin sin) + i (cos sin + sin
cos)

By the addition formulas for sine and cosine the right side of this is equal to the right side
of (6). //

6.5 - 5